Organic Chilli Pepper (Capsicum annuum cv. Superhot) Quality and Biochemical Responses to Sequential Treatment with Hot Water, Surface Coating, Equilibrium Modified Atmosphere Packaging and Cold Storage - Wiraya Krongyut; Rachen Duangsi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Organic chilli peppers (Capsicum annuum cv. Superhot) at full-red stage were submeged in 50°C water for 4 minutes followed by surface coating with carboxymethyl cellulose (CMC) or chitosan at 0.25-1.0% for 2 minutes. The fruits were then packed in 32-34 µm thick polyethylene bag (Active PAKTM) before cold storage at 10°C for 12 days followed by 5 days holding at 25°C. The decrease of fruit quality was due to weight loss and decay and these could be reduced by edible coating. Coated fruit had higher titratable acidity, vitamin C content, total phenols, and activities of phenylalanine ammonia lyase, superoxide dismutase and catalase as compared to uncoated fruit. Chitosan was more effective than CMC in bringing these effects, and 0.5% was the most effective concentration. The results indicated that fruit coating by 0.5% chitosan and CMC maintained quality of chilli peppers by slowing physicochemical quality changes and improving the antioxidant system.